Pengaruh Lingkungan Kerja, Stres Kerja, Dan Disiplin Kerja Terhadap Kinerja Karyawan - Karina Ayu Wardani; Kasmari Kasmari (Peneliti.net, 2023)
This research intends to understand the impact of the work environment, work stress and work discipline on the performance of production employees at PT. Semarang City Nuclear Coating Fabric. This type of research is quantitative research using a tool in the form of a questionnaire. The population in this study used a sample of 125 production employees. The analysis technique used in this study is multiple linear regression analysis. The sampling technique uses a purposive sampling technique. The data in this study were processed using SPSS version 22. Data were analyzed using factor analysis to test the validity of each question item and Cronbach alpha to test reliability. The results of hypothesis testing show that the work environment has a positive and significant impact on employee performance, work stress has a negative and insignificant impact on employee performance work discipline has a positive and significant impact on employee performance